Word of mouth marketing : how smart companies get people talking - Sernovitz, Andy. (Austin, TX : Greenleaf Book Group Press, 2012)
Offers advice for using the power of word-of-mouth recommendations to gain the attention of customers by producing the type of product or becoming the type of organization that people want to spread the word about.